Studi komparasi kejadian asfiksia berdasarkan waktu induksi pada kemanilan postterm di RSUD Kebumen - Winarni Winarni; Suherni Suherni; Yuni Kusmiyati (Poltekkes Kemenkes Yogyakarta, 2012)
There are 146,000 dead babies every year,401 babies die every day or 17 babies die every hour. Millenium Development Goals Target (MDGs) in the year 2015, the infant Mortality Rate (IMR) will decease from 34/1,000 alive birth into 23/1,000 alive birth. The most dead babies cause is asphyxia (34%). One of the risk factors of asphyxia is post-term pregnancy. Objective: To know the asphyxia happening difference between induction of labor at the 41 weeks pregnancy age with the induction of labor at 42 weeks pregnancy age in the Govemment Public Hospital (RSUD) of Kebumen in the year 2010-2011. Method: This research used analytical observasional by applying case control approach. The research population was all new born babies from induction of labour at postterm pregnancy in Kebumen Goverment Public Hospital in the year 2010-2011. Sample taking used purposive sampling on 74 subjects for case group and 74 subjects control group. The analytical test used Chi-Square on the trust level of 95%. Result: Chi-Square analysis got 0.013 p-value, it meant that there was the difference of asphyxia happening between the induction of labour 41 weeks pregnancy age with the induction of labour at 42 weeks pregnancy age. The asphyxia happening at induction of labour 41 weeks pregnancy age was 39.1%, whereas 42 weeks pregnancy age was 59.5%.